Potential to use metaverse for future teaching and learning - Onu, Peter; Pradhan, Anup; Mbohwa, Charles (Education and information technologies, 2024)
Metaverse, a virtual shared space integrating augmented reality and virtual reality technologies, is often hailed as the “Internet of the future” for its potential to revolutionize online communication, collaboration, learning, and work. However, despite its promising strategic and business applications, there is a dearth of empirical evidence for evaluating its educational value. This qualitative study examined the impact of Metaverse on teaching and learning by examining its advantages and challenges. The outcomes highlight Metaverse’s remarkable potential for personalized and adaptive learning thanks to its immersive and interactive capabilities. An analysis of the existing literature suggests that Metaverse can create engaging learning experiences in which students can explore tailored virtual environments and interact within them. Semi-structured in-depth interviews were conducted to confirm the perception of metaverse-based education among students, educators, and program administrators, who view it as an innovative and effective educational delivery method. Several barriers require attention to ensure the successful integration of Metaverse in education, such as network connectivity, reliability, standardization and certification, organizational readiness, and the specialized skills necessary to leverage Metaverse’s potential. This study offers a comprehensive understanding of Metaverse’s potential, limitations, and critical factors contributing to its education success. By providing immersive and interactive learning experiences tailored to individual student needs, Metaverse holds the power to revolutionize teaching and learning. However, addressing challenges related to interoperability and the need for more evidence on its efficacy requires further research and development efforts. The significance of this study hinges on the continued exploration of Metaverse to enhance educational experiences, offering a novel and innovative approach to teaching and learning.